2019
DOI: 10.1136/annrheumdis-2019-215894
|View full text |Cite
|
Sign up to set email alerts
|

Global skin gene expression analysis of early diffuse cutaneous systemic sclerosis shows a prominent innate and adaptive inflammatory profile

Abstract: ObjectivesDetermine global skin transcriptome patterns of early diffuse systemic sclerosis (SSc) and how they differ from later disease.MethodsSkin biopsy RNA from 48 patients in the Prospective Registry for Early Systemic Sclerosis (PRESS) cohort (mean disease duration 1.3 years) and 33 matched healthy controls was examined by next-generation RNA sequencing. Data were analysed for cell type-specific signatures and compared with similarly obtained data from 55 previously biopsied patients in Genetics versus En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 32 publications
(47 reference statements)
6
103
1
Order By: Relevance
“…5a, b, P value = 0.0001, one-sided Mann-Whitney U test). Gene expression profiles from multiple published studies 26,33,34 have also shown that gene ZBTB46 were significantly higher expressed in SSc skin versus normal skin ( Fig. 5c, P value = 0.0002, 0.003, 0.00001, one-sided Mann-Whitney U test).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…5a, b, P value = 0.0001, one-sided Mann-Whitney U test). Gene expression profiles from multiple published studies 26,33,34 have also shown that gene ZBTB46 were significantly higher expressed in SSc skin versus normal skin ( Fig. 5c, P value = 0.0002, 0.003, 0.00001, one-sided Mann-Whitney U test).…”
Section: Resultsmentioning
confidence: 70%
“…The time points Low and High can be different for different patients. In this analysis, 13 patients whose highest mRSS -lowest mRSS > 5 were included (patients' ID 03, 04, 05, 06, 10,16,17,21,30,33,37,42,45).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Functional defects or genetic susceptibility variants located in relevant genes for dendritic cells, macrophages and B cells have been described in patients with SSc. [39][40][41][42][43] T cell subtypes were relevant covariates in the model initially, but no T cell subset was selected for the multivariate model (online supplemental tables 2-4). Considering the central role of T cells in SSc, we hypothesise that since we could not include the Th1, Th2 or Th17 fractions in the model, this effect might have been overlooked.…”
Section: Discussionmentioning
confidence: 99%